Some Methods & Equipment for Run-off Measurements from Small Watersheds - Ullah, Wasi; Dalal, S. S. (Indian Forester, 1967)
The paper describes the technique used, the standards of accuracy followed and experience gained in measurement and analysis of run-off from small watersheds, at the Central Soil Conservation Research Demonstration and Training Centre, Dehra Dun. Nine watersheds from 2.5 acres to 200 acres are under gaging. Precalibrated triangular weirs and H Flumes have been used as artificial control. A sediment basin was found essential in one watershed, where excessive sedimentation disturbed the cross section of the approach channel. The sources of error and precautions essential for ensuring a high degree of accuracy in run-off measurement have been outlined, The following standards of reading discharge from the rating table have been followed: Less than 1 cusec - up to 3 decimal places Less than 10 cusecs- " 2 " Less than 100 " - " 1 " More than 100" - wbole figure The field checking of the laboratory rating of weirs has not been found practicable due to flashy flows. But the desirability of checking these ratings in the field should be kept in view wherever possible. Four different types of stage recorders are in use and their specifications are given. The weak spring mechanism of the clocks of local stage recorded resulted in relatively more frequent repairs. The techniques of data processing used at this Research Station have been briefty mentioned. Correction for time error has been applied, whereas no correction for gage and chart expansion errors have been found necessary. The paper brings out clearly the accuracy standards necessary for computing the run-off data. The accuracy attempted during the data processing and reduction should be in proportion to the accuracy standards possible to measure run-off in the field.